Sialylation of chitosan to mitigate Aβ toxicity - Dhruva Dhavale (2023)
Amyloid beta peptide (Aβ) is the main component of plaques and is known to play a role in the development of Alzheimer's disease (AD). As a result, structures that can trap Aβ or disrupt the interaction between Aβ and cells have been researched as a way to lessen the pathological effects of Aβ. Particularly, sialylated compounds that exhibit clustering effects could be advantageous.